Pemertahanan Bahasa dan Identitas Linguistik Remaja Kazakh di Bayan-Ölgii: Kajian Etnolinguistik dengan Kerangka Fishman dan Edwards - Viki Mayanfa'uki; Amir Maliki Abitolkha; Vina Nur 'Afiyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT Mongolia’s language policy, which designates Mongolian as the state language and main medium of instruction, has affected the vitality of the Kazakh language in Bayan-Ölgii. This study examines the implications of this policy on the linguistic identity of Kazakh adolescents using an ethnolinguistic approach. Drawing on Fishman’s framework of language maintenance and shift and Edwards’ theory of language and group identity, this study synthesizes literature and education reports from 2005–2025. The findings show that the formal education domain has undergone Mongolization: Mongolian dominates core subjects, examinations, and certification, while Kazakh is reduced to a subject with limited hours. In contrast, Kazakh remains strong in family and community domains as a symbol of ethnicity, family closeness, and Islamic affiliation. This condition produces asymmetrical bilingualism and dual linguistic identities that adolescents negotiate at school, at home, and in digital spaces. The article recommends mother-tongue-based bilingual education, Mongolian-as-a-second-language teacher training, and support for Kazakh-language digital ecosystems to slow language shift and strengthen Kazakh maintenance in Mongolia. Keywords : asymmetrical bilingualism, Bayan-Ölgii, Kazakh minority, language identity, language maintenance